Research Handbook on Islamic Law and Society : By Nadirsyah Hosen, ed. (Cheltenham, UK: Edward Elgar Publishing, 2018. 485 pages.) (American Journal of Islam and Society, 2019)
The premise of the adaptability, flexibility, and compatibility of Islamic normative teachings (sharīʿa) to new social contexts is already documented by many scholars, including John Bowen’s On British Islam: Religion, Law, and Everyday Practice in Shari‘a Councils and Michael G. Peletz’s Islamic Modern: Religious Courts and Cultural Politics in Malaysia. Unlike those works, this textbook is organized by theme which provides a unique contribution to our understanding of the overall function of contemporary Islamic law. Such an approach shows that the ‘right’ answer in one country is not necessarily the ‘right’ solution in another Muslim community, which explains the diverse application of Islamic law. The book challenges Wael Hallaq’s observation that the modern codification of Islamic law resulted in the absence of hermeneutical possibilities or led to a single mode of judicial application. Perhaps Hallaq’s proposition is accurate if we examine the function of Islamic law in a specific country. Nevertheless, the book provides concrete examples of the administrative and interpretive techniques of ‘neo-ijtihād’ today.To download full review, click on PDF.